2014
DOI: 10.1155/2014/152063
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizae Radix Methanol Extract Attenuates Methamphetamine‐Induced Locomotor Sensitization and Conditioned Place Preference

Abstract: Glycyrrhizae Radix modulates the neurochemical and locomotor alterations induced by acute psychostimulants in rodents via GABAb receptors. This study investigated the influence of methanol extract from Glycyrrhizae Radix (MEGR) on repeated methamphetamine- (METH-) induced locomotor sensitization and conditioned place preference (CPP). A cohort of rats was treated with METH (1 mg/kg/day) for 6 consecutive days, subjected to 6 days of withdrawal, and then challenged with the same dose of METH to induce locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…In the meantime, in the above mentioned studies, we have shown that G. radix exerts its neuropharmacological actions via glutamatergic and gamma-aminobutyric acid (GABA)ergic receptors [ 19 , 21 ], which is also supported by the study done by others [ 24 ]. However, since the primary pharmacological property of G. radix is its antioxidant capabilities, and as reported by Zeng et al that isoliquiritigenin alleviated intracerebral hemorrhage-induced brain injury in rats via suppressing excessive ROS production [ 25 ], it is possible that the neuroprotective effects of G. radix against repeated psychostimulant treatment are mediated, at least in part, via its antioxidant activities.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the meantime, in the above mentioned studies, we have shown that G. radix exerts its neuropharmacological actions via glutamatergic and gamma-aminobutyric acid (GABA)ergic receptors [ 19 , 21 ], which is also supported by the study done by others [ 24 ]. However, since the primary pharmacological property of G. radix is its antioxidant capabilities, and as reported by Zeng et al that isoliquiritigenin alleviated intracerebral hemorrhage-induced brain injury in rats via suppressing excessive ROS production [ 25 ], it is possible that the neuroprotective effects of G. radix against repeated psychostimulant treatment are mediated, at least in part, via its antioxidant activities.…”
Section: Introductionmentioning
confidence: 73%
“…In previous studies, we found extracts from G. radix suppressed acute cocaine- and methamphetamine- induced increases in accumbal DA levels [ 19 ] and prevented acute methamphetamine-induced hyperlocomotion in rats [ 20 ], indicating inhibitory effects of G. radix against pharmacological actions of psychostimulants. Moreover, in other studies, we also demonstrated G. radix improved the behavioral and neurochemical abnormalities caused by repeated psychostimulant treatment such that extracts from G. radix attenuated methamphetamine-induced locomotor sensitization and conditioned place preference [ 21 ] and isoliquiritigenin ameliorated repeated methamphetamine-induced loss of striatal dopamine transporter densities and tyrosine hydroxylase activities [ 22 ]. Since nicotine belongs to the category of psychostimulants and shares common neurochemical and behavioral traits with the typical psychostimulants when given repeatedly [ 23 ], the results of these studies collectively raise the possibility that G. radix can prevent the occurrence of aberrant neurochemical and behavioral changes by RNT.…”
Section: Introductionmentioning
confidence: 90%
“…Drug‐induced behaviorally sensitized animal models are used routinely to define the cellular and molecular mechanisms underlying drug addiction and associated psychomotor behavioral alternations (Collins et al, ), and relevant tools have been developed to this effect (Kai, Nishizawa, Tsutsui, Ueda, & Kobayashi, ; Mohd‐Yusof et al, ). Further, pharmaceutical interventions can be introduced during the development of behavioral sensitization to evaluate the therapeutic effect on behavioral sensitization and reinstatement (Song et al, ; Sun et al, ; Zhao et al, ). The principal preclinical animal models of behavioral sensitization were rats (Mohd‐Yusof et al, ; Song et al, ; Zhao et al, ) and mice (Kai et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, pharmaceutical interventions can be introduced during the development of behavioral sensitization to evaluate the therapeutic effect on behavioral sensitization and reinstatement (Song et al, ; Sun et al, ; Zhao et al, ). The principal preclinical animal models of behavioral sensitization were rats (Mohd‐Yusof et al, ; Song et al, ; Zhao et al, ) and mice (Kai et al, ; Sun et al, ). Considering the significant differences in neuroanatomic structures and the functional divergence of the nervous systems of rodents and humans, however, these rodent‐based models may contribute limited understandings of addictive drugs' neurotoxicity and addictive behaviors in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation